A Plataforma Lattes como recurso estratégico para a gestão dos Programas de Pós-Graduação: uma análise baseada na produção de artigos científicos - Maciel, Raquel Santos (Universidade Federal de São Carlos, 2018)
Bibliometric analyzes of the scientific production have great adherence in the area of Information Science for the possibility of establishing profiles of the scientific activity and allow the decision on the allocation of resources with regard to the management of the graduate programs. In this sense, this research analyzes the Lattes Platform as a strategic resource to subsidize the periodic partial monitoring of the intellectual production of the postgraduate programs of the Brazilian higher education institutions, taking as a parameter the recommendations of the National Postgraduate Plan regarding the indicators aimed at improving concepts. Among these indicators, those that stand out in the Assessment Sheet - an instrument used in the evaluative process of the masters and doctoral courses - are the four indicators: Intellectual Production, in its subitem articles published in periodicals. Quantitative approach, applied nature and exploratory and descriptive character, this research has as general objective to develop a systematic for the elaboration and analysis of bibliometric indicators related to the production of scientific articles of professors accredited in postgraduate programs. The postgraduate programs of the Federal University of São Carlos were chosen as units of application of this systematics, as well as the subunits of application were the Graduate Programs in Science and Engineering of Materials, in Education and in Information Science. The methodological procedures involved the SyncLattes and VantagePoint softwares for the collection, data processing and elaboration of bibliometric indicators, with a total of 16,275 bibliographic records related to the scientific articles published in the period 2010-2017 by 48 programs in operation in the year 2016. They were elaborated indicators related to the average annual production of articles for the three-year period 2010-2012 and the quadrennium 2013-2016, in addition to the quantity of articles published in the year 2017, in order to allow the monitoring of the production of articles in their quantitative aspect. As regards the qualitative aspect, the Qualis Periodic evaluation instruments were used as reference, which establish eight strata - A1, A2, B1, B2, B3, B4, B5 and C - to classify the intellectual production published in scientific journals. Thus, it was possible to characterize the production of articles studied in connection with one of the aspects of the evaluation process, which can contribute to the decision-making in a timely manner and to the management in the scope of graduate programs. From the results, it is intended to increase the visibility of the Lattes Platform as an important strategic resource, since it provides data on the most diverse types of publications in a global way, which can contribute to the management of graduate programs and the institution itself.
The Lattes Platform as a strategic resource for the management of postgraduate programs: an analysis based on the production of scientific articles
Keywords: Universidade Federal de São Carlos; Programas de pós-graduação; Plataforma Lattes; Avaliação da pós-graduação; Bibliometria; Indicadores bibliométricos; Federal University of São Carlos; Graduate programs; Lattes Platform; Postgraduate evaluation; Bibliometric; Bibliometric indicators; UFSCar; Universidad Federal de San Carlos; Programas de postgrado; Evaluación del postgrado; Bibliometría; CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO::BIBLIOTECONOMIA::METODOS QUANTITATIVOS. BIBLIOMETRIA